A case report of an abnormal trend in hCG levels in a pregnancy complicated by ovarian hyperstimulation syndrome - Ariel Benor; Richard Grazi; David Kulak (Elsevier, 2019)
Objective: To present a case of abnormally trending hCG levels due to ovarian hyperstimulation syndrome (OHSS) and to portray the obscurities of this commonly used method for tracking early pregnancies. Design: Case report. Setting: Outpatient ART facility. Patient: A patient who received controlled ovarian hyperstimulation in an ART cycle. Intervention: Supportive care. Main outcome measure: hCG level. Result: The hCG levels in this patient with OHSS trended in an abnormal fashion, suggesting a failing or ectopic pregnancy, but the patient had a normal intrauterine fetus. Conclusion: hCG levels may be falsely low in pregnancies complicated by OHSS. Keywords: OHSS, hCG, Early pregnancy, Abnormal trend